Grief in Response to Uncertainty Distress Among Veterinary Students During the Early Stages of the COVID-19 Pandemic - Carney, Kimberly; Thompson, R. Randall (Frontiers in Veterinary Science, 2021)
The abrupt and life-altering shifts brought on by the COVID-19 pandemic have stimulated research in fields ranging from social sciences to virology. This study explored perceptions and experiences of COVID-19's impact on students at Lincoln Memorial University–College of Veterinary Medicine (LMU-CVM) and considered how to respond to these. Semistructured interviews were conducted with 20 students from LMU-CVM. Thematic analysis elucidated five subthemes that were combined into two main themes based on Bertuccio's framework of grief in response to uncertainty distress. Uncertainty and disruption of routine were subthemes of ambiguous loss, while lost opportunities, milestones missed, and risk concern came under anticipatory grief. There was overlap and fluidity within these themes, with frustration, stress, and unexpected benefits pervading all categories. Differences were noted between classes, with clinical students expressing concern over graduation and lack of preparedness, and preclinical students with online assessment, lost opportunities for clinical experiences, and the loss of social connections. These results point to mitigation strategies for the adverse effects of COVID-19-related stressors specific to this population that encompass academic, physical, and mental well-being concerns. Clear communication, assurance of quality education, flexibility for meeting family needs, financial assistance, and mental health support are the areas evident from the interviews where successful responses might be targeted. This study also highlights areas for future research, including follow-up interviews, given the prolonged timeline of COVID-19, surveys of beliefs and practices across a larger university population, and exploration of the long-term impact on academic and practice success of the affected cohorts.